ANALISIS KINERJA PEGAWAI BERDASARKAN BUDAYA KERJA APARATUR SIPIL NEGARA: (Studi Dinas Perumahan, Permukiman, Cipta Karya Dan Tata Ruang Kabupaten Sidoarjo Bidang Tata Ruang) - Alfan Alfan Fajar Imansyah; Djoko Widodo; Muchammad Wahyono (COMMUNITY OF RESEARCH LABORATORY SURABAYA)
The researcher's initial observations show that the Department of Housing, Settlements, Cipta Karya and Spatial Planning of Sidoarjo Regency in the Spatial Planning Sector has not implemented a good performance. The purpose of this study was to determine and analyze employee performance based on the work culture of the state civil apparatus in the Spatial Planning of the Housing, Settlement, Cipta Karya and Spatial Planning Office of Sidoarjo Regency. The data analysis technique used in this study uses the Miles and Huberman model. The results of the study indicate that the work culture in the Spatial Planning sector has an effect on employee performance. The research findings indicate that the indicator of a lack of work culture is employee discipline. There are still some employees who are inconsistent in terms of punctuality in entering office hours. Although the human resources are complete in the field of spatial planning, in the eyes of the community it seems to delay the service time. The presence of time delays when entering office hours makes the performance of employees in the Spatial Planning sector considered less by the public which ultimately creates a negative stigma to Spatial Planning employees.